Maisir in Online Gaming Business: A Theological and Islamic Ethical Perspective - Denis Sasmita; Eka Maulana; Sumarta (Penerbit Hellow Pustaka, 2025)
Modern derivative markets provide flexibility and risk management but pose challenges for Sharia compliance due to potential gharar (uncertainty) and maysir (speculation). This study employs a library research approach to evaluate the conformity of conventional derivatives with Islamic law principles in Indonesia. The analysis highlights that futures, options, and swaps rely on price predictions without actual asset ownership, risking violations of al-mal and al-bay’ principles. National regulations, including DSN-MUI Fatwa No. 80/DSN-MUI/III/2011, OJK, and BEI, have not explicitly addressed Sharia-compliant derivatives, while public literacy remains low. Alternatives through salam, istisna’, and urbun contracts show potential for real-based derivative contracts that minimize gharar and maysir while adhering to Sharia principles. Financial technologies such as blockchain and smart contracts can enhance transparency, efficiency, and compliance. Practical implications include strengthening Sharia derivative regulations, increasing digital literacy and public education, and innovating products responsive to domestic and global market needs. Through collaborative strategies among regulators, academics, industry, and religious authorities, Sharia derivatives can become strategic instruments to expand financial inclusion, strengthen market integrity, and support the growth of Indonesia’s Islamic finance industry. This study provides a conceptual foundation for regulation development, instrument design, and public education regarding Sharia derivatives in Indonesia